Mutant monocyte chemoattractant protein 1 protein attenuates migration of and inflammatory cytokine release by macrophages exposed to orthopedic implant wear particles. Issue 9 (20th November 2013) - Yao, Zhenyu; Keeney, Michael; Lin, Tzu‐Hua; Pajarinen, Jukka; Barcay, Katherine; Waters, Heather; Egashira, Kensuke; Yang, Fan; Goodman, Stuart
Abstract Wear particles generated from total joint replacements can stimulate macrophages to release chemokines, such as monocyte chemoattractant protein 1 (MCP‐1), which is the most important chemokine regulating systemic and local cell trafficking and infiltration of monocyte/macrophages in chronic inflammation. One possible strategy to curtail the adverse events associated with wear particles is to mitigate migration and activation of monocyte/macrophages. The purpose of this study is to modulate the adverse effects of particulate biomaterials and inflammatory stimuli such as endotoxin by interfering with the biological effects of the chemokine MCP‐1. In the current study, the function of MCP‐1 was inhibited by the mutant MCP‐1 protein called 7ND, which blocks its receptor, the C–C chemokine receptor type 2 (CCR2) on macrophages. Addition of 7ND decreased MCP‐1‐induced migration of THP‐1 cells in cell migration experiments in a dose‐dependent manner. Conditioned media from murine macrophages exposed to clinically relevant polymethylmethacrylate (PMMA) particles with/without endotoxin [lipopolysaccharide (LPS)] had a chemotactic effect on human macrophages, which was decreased dramatically by 7ND. 7ND demonstrated no adverse effects on the viability of macrophages, and the capability of mesenchymal stem cells (MSCs) to form bone at the doses tested. Finally, proinflammatory cytokine production was mitigated when macrophages were exposed to PMMA particles with/without LPS in the presence of 7ND. Our studies confirm that the MCP‐1 mutant protein 7ND can decrease macrophage migration and inflammatory cytokine release without adverse effects at the doses tested. Local delivery of 7ND at the implant site may provide a therapeutic strategy to diminish particle‐associated periprosthetic inflammation and osteolysis. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3291–3297, 2014.